A dysregulated acetyl/SUMO switch of FXR promotes hepatic inflammation in obesity - Kim, Dong-Hyun (EMBO J, 2015)
Acetylation of transcriptional regulators is normally dynamically regulated by nutrient status but is often persistently elevated in nutrient-excessive obesity conditions. We investigated the functional consequences of such aberrantly elevated acetylation of the nuclear receptor FXR as a model. Proteomic studies identified K217 as the FXR acetylation site in diet-induced obese mice. In vivo studies utilizing acetylation-mimic and acetylation-defective K217 mutants and gene expression profiling revealed that FXR acetylation increased proinflammatory gene expression, macrophage infiltration, and liver cytokine and triglyceride levels, impaired insulin signaling, and increased glucose intolerance. Mechanistically, acetylation of FXR blocked its interaction with the SUMO ligase PIASy and inhibited SUMO2 modification at K277, resulting in activation of inflammatory genes. SUMOylation of agonist-activated FXR increased its interaction with NF-κB but blocked that with RXRα, so that SUMO2-modified FXR was selectively recruited to and trans-repressed inflammatory genes without affecting FXR/RXRα target genes. A dysregulated acetyl/SUMO switch of FXR in obesity may serve as a general mechanism for diminished anti-inflammatory response of other transcriptional regulators and provide potential therapeutic and diagnostic targets for obesity-related metabolic disorders.